Gastroprotective effect of the Lachnum polysaccharide and polysaccharide-dipeptide conjugates against gastric ulcer. (April 2023) - Zhang, Xinmiao; Liu, Dong; Ye, Ziyang; Chen, Xue; Chen, Hui; Ye, Ming
Abstract: Polysaccharides from Lachnum have many important biological activities. The LEP2a-dipeptide derivative (LAG) was obtained by carboxymethyl modification and alanyl-glutamine modification of LEP2a, an extracellular polysaccharide component of Lachnum . Mice with acute gastric ulcers were treated with 50 (low doses) and 150 (high doses) mg/kg, and their therapeutic effects were evaluated from the aspects of pathological damage to gastric tissue, oxidative stress response and inflammatory signal cascade reaction. High doses of LAG and LEP2a significantly inhibited pathological damage to the gastric mucosa, increased the activities of SOD and GSH-Px, and decreased the levels of MDA, and MPO. LEP-2A and LAG could also inhibit the production of proinflammatory factors and reduce the inflammatory response. They significantly decreased the levels of IL-6, IL-1β and TNF-α, while upregulated the level of PGE2 at high doses. LAG and LEP2a inhibited the protein expression of p-JNK, p-ERK, p-P38, p-IKK, p-IKB α and p-NF-KBP65. LAG and LEP2a protect the gastric mucosa in mice with ulcers by improving oxidative stress, blocking the MAPK/NF-κB pathway and inhibiting the production of inflammatory factors, and the anti-ulcer activity of LAG is superior to that of LEP2a.